Analisis Nilai Pendidikan Karakter dalam Teks Sastra pada Buku Bahasa Indonesia Kelas VII Kurikulum 2013 - Andi Magfirahwati J.; Muhammad Saleh; Usman Usman (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
Abstract. This study aims to describe the manifestation of character education values based on the guidelines for strengthening character education in 2018 contained in the literary text of the Indonesian Language Book Class VII SMP/MTs Curriculum 2013 revision 2017. This study uses a descriptive qualitative method. The data of this research are literary texts in Indonesian Language Book Class VII SMP/MTs Curriculum 2013 revision 2017 namely fantasy texts, folk poetry texts, and fable texts. The data collection technique used in this research is library research and documents. The results of the study show that 1) The form of character education values based on the guidelines for strengthening character education in 2018 in the fantasy story text of Indonesian Language Book Class VII SMP/MTs Curriculum 2013 there are five character education values with fifteen sub-values. The values of character education in the fantasy text of the book include religious, nationalist, independent, mutual cooperation, and integrity values. 2) In folk poetry there are four values of character education with ten sub-values. The values of character education in the text of the book's folk poetry include religious, nationalist, independent, and integrity values. 3) In the fable text there are five values of character education with twenty sub-values. The form of character education values in the book's fable text includes religious, nationalist, independent, mutual cooperation, and integrity values.Keywords: Education, Character, Literary Text